Matemáticas
jenyandrea10
2

Mega Urge!! ECUACIONES. a) 6(7-x)= 8 (6-x) b) -8 ( 10 - x ) = -6 c) (x+2) . 3 = (13-x) .4 +3 d) 3( 1 -2x) + 12 = 10 - 2 (x-3) e) 4 (x-6) = 12 - (x +3) f) -2 (x + 3 ) -4 = 18 + 4 x g) 2 (3x+1) -x +6 =2 (x-1) h) 6x - 2 (x-3) =12

+0
(1) Respuestas
cgreyes

a) 6 (7-x) = 8 (6-x) 42 -6x = 48 -8x -6x +8x = 48 -42 2x = 6 x = 6/2 x = 3 b)  -8 ( 10 - x ) = -6 -80 +8x = -6 8x = -6 +80 8x = 74 x = 74/8 x = 37/4 c) (x+2) . 3 = (13-x) .4 +3 3x +6 = 52 -4x +3 3x +4x = 52 +3 -6 7x = 49 x = 49/7 x = 7 d) 3( 1 -2x) + 12 = 10 - 2 (x-3) 3 -6x +12 = 10 -2x +6 3 +12 -10 -6 = -2x +6x -1 = 4x -1/4 = x x = -1/4 e) 4 (x-6) = 12 - (x +3) 4x -24 = 12 -x -3 4x +x = 12 -3 +24 5x = 33 x = 33/5 f)  -2 (x + 3 ) -4 = 18 + 4 x -2x -6 -4 = 18 +4x -6 -4 -18 = 4x -2x -28 = 2x -28/2 = x -14 = x x = -14 g) 2 (3x+1) -x +6 =2 (x-1) 6x +2 -x +6 = 2x -2 6x -x -2x = -2 -6 -2 3x = -10 x = -10/3 h) 6x - 2 (x-3) =12 6x -2x +6 = 12 6x -2x = 12 -6 4x = 6 x = 6/4 x = 3/2

Añadir respuesta